2015
DOI: 10.1186/s12953-015-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

The calcified eggshell matrix proteome of a songbird, the zebra finch (Taeniopygia guttata)

Abstract: BackgroundThe proteins of avian eggshell organic matrices are thought to control the mineralization of the eggshell in the shell gland (uterus). Proteomic analysis of such matrices identified many candidates for such a role. However, all matrices analyzed to date come from species of one avian family, the Phasianidae. To analyze the conservation of such proteins throughout the entire class Aves and to possibly identify a common protein toolkit enabling eggshell mineralization, it is important to analyze eggshe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 126 publications
(195 reference statements)
2
45
0
Order By: Relevance
“…Therefore, being calcite the most stable polymorph, RNA and gDNA induce mainly the formation of this polymorph in the different structures of organisms, ensuring in this way the biological perpetuation of a species. As indicated previously, the calcite polymorph is part of echinoderms, sea urchins, ophiuroids, sea cucumbers, crinoids; arthropods like trilobites; mollusks like bivalves, gastropods, polyplacophorans, ammonoids, or nautiloids; calcareous seashells; and spicules of sponges, algae, eggshells, teeth, bones, and otoliths [23][24][25]50,51]. Calcium, besides forming part of the support structures of organisms, is also very important for cellular metabolism.…”
Section: In the Presence Of Nucleic Acids Calcium Is The Element Thamentioning
confidence: 72%
“…Therefore, being calcite the most stable polymorph, RNA and gDNA induce mainly the formation of this polymorph in the different structures of organisms, ensuring in this way the biological perpetuation of a species. As indicated previously, the calcite polymorph is part of echinoderms, sea urchins, ophiuroids, sea cucumbers, crinoids; arthropods like trilobites; mollusks like bivalves, gastropods, polyplacophorans, ammonoids, or nautiloids; calcareous seashells; and spicules of sponges, algae, eggshells, teeth, bones, and otoliths [23][24][25]50,51]. Calcium, besides forming part of the support structures of organisms, is also very important for cellular metabolism.…”
Section: In the Presence Of Nucleic Acids Calcium Is The Element Thamentioning
confidence: 72%
“…We also identified several egg yolk (vitellogenin 1, VTG1 ) and egg white (hen egg white 21, HEP21 ) proteins with higher abundance in the outer eggshell. Previous studies found VTG1 in both chicken eggshell and uterine fluid . Currently, there is no obvious role for VTG1 in eggshell formation.…”
Section: Resultsmentioning
confidence: 90%
“…EV localization was predicted using molecular function of proteins on Uniprot (https://www.uniprot.org/). References:(32)(33)(34)(35)(62)(63)(64)(65)67,(69)(70)(71)(72)(73)(74)(75)(76)(77)(78).…”
mentioning
confidence: 99%